MATHEMATICAL MODEL OF PURIFICATION PROCESS OF OIL CONTAMINATED WATERS - Бойченко, С.; Кучер, О.; Павлюх, Л. (Proceedings of National Aviation University (archive), 2012)
Sorption properties of carbonic sorbents on natural raw materials for purification of waste waters frompetroleum products are investigated. Temperature influence on sumption properties of sorbents on naturalraw materials to increase the purification degree of water ecosystem is studied. Mathematical model ofpurification process of oil contaminated waters is developed